2007
DOI: 10.2116/analsci.23.1245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Behavioral Differences between Native Polycyclic Aromatic Hydrocarbons and 13C-Labeled Internal Standards during Clean-up Steps of Analysis

Abstract: We confirmed that concentrations of polycyclic aromatic hydrocarbons (PAHs) obtained by isotope dilution mass spectrometry (IDMS) using the corresponding 13 C-labeled internal standards are reliable even after clean-up steps. Change in the ratio of phenanthrene to 13 C6-phenanthrene was less than 0.2%, although the recovery yield of 13 C6-phenanthrene decreased to 60%. Since changes in the ratios were commonly within the relative standard deviations of the concentrations (1.5 -5.4%) obtained using gas chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The experimental isotope abundances at a given mass were calculated by dividing the peak area of that mass in the mixture by the sum of all areas. The molar fractions x nat and x lab were calculated using eqns (7) and (8). Matrix A corresponded to the values shown in Table 2 and Fig.…”
Section: Application Of Multiple Linear Regression In Idmsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental isotope abundances at a given mass were calculated by dividing the peak area of that mass in the mixture by the sum of all areas. The molar fractions x nat and x lab were calculated using eqns (7) and (8). Matrix A corresponded to the values shown in Table 2 and Fig.…”
Section: Application Of Multiple Linear Regression In Idmsmentioning
confidence: 99%
“…In general, the concentration of the labelled compound will be calculated from reverse isotope dilution experiments and its final uncertainty will show a contribution of the uncertainty in the concentration of the natural abundance standard. The second important source of uncertainty in the multiple linear regression procedure is the isotope composition of both natural abundance and labelled compounds which are used to construct the matrix A in eqns (7) and (8). In our case, the uncertainties in the isotope composition of the natural and labelled compounds should take into account also the uncertainties in the fragmentation factors as shown in Table 2.…”
Section: Calculation Of Uncertainty Budgets and Evaluation Of Uncertamentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Although one study found that ultrasonic extraction can obtain comparable yields to those obtained by other techniques, 14 another found that this procedure is not as efficient at extracting BaP as Soxhlet extraction. 15 Although both Soxhlet extraction [16][17][18][19] and PLE 20 have also been used to determine PAHs in sediments collected in Japan, differences in the yields of PAHs obtained by PLE and the Japanese official method can be expected to be the largest among extraction methods if they occur. 20 In this study, we optimized the temperature and pressure of extraction by PLE.…”
Section: Introductionmentioning
confidence: 99%